The relationship between the gut microbiome and the aqua cultured fish, general prospects toward fish health: A systematic review - Darren Dean Tay; Vijay Subbiah Kumar; Rossita Shapawi; Muhammad Dawood Shah; Hajar Fauzan Ahmad; Nurzafirah Mazlan (Humana Press, 2025)
Aquaculture allows the cultivation of aquatic life outside its normal origins which can pro- vide work opportunities, seafood security, as well as conservation efforts for endangered fish species. Numerous factors influence the health of aquaculture fish, with the gut micro- biome playing a pivotal role. Research indicates that an imbalance or dysbiosis in the gut microbiome can significantly affect the overall well-being and health outcome of these fish. Despite extensive research utilizing metagenomics across diverse environments and con- trolled conditions, a clear consensus on the characteristic of “healthy” or “optimal” gut microbiome in domesticated fish has yet to be established. This review will cover 28 studies, which further discusses the findings of the gut microbiome within fish and attempts to provide a general outline of how the gut bacteria may interact and affect fish health within aquaculture environments. The indices as well as pathogens and beneficial bacteria of each study are also listed. This review aims to provide readers with an enhanced understanding of the complex dynamics of the gut microbiome in aquaculture fish, while offering insights that could inform the design of future studies in this field.